Security by Other Means : Foreign Assistance, Global Poverty, and American Leadership - Brainard, Lael (Book collections on Project MUSE., 2007)
"Assesses the current structures of foreign assistance and makes recommendations for efficient coordination. Drawing on expertise from the full range of foreign aid agencies, examines foreign assistance across four categories: security, economic, humanitarian, and political"--Provided by publisher